KERANCUAN FONO-ORTOGRAFIS DAN ORTO-FONOLOGIS BAHASA INDONESIA RAGAM LISAN DAN TULIS - -, Soeparno (Diksi, 2005)
This article is based on a research conducted within a limitedscope (that is, within the community of the state university knownas Universitas Negeri Yogyakarta) on some phonoorthographicandortho-phonologic ambiguity found in spoken and written varietiesof Indonesian. By means of comparisons followed with sociophonologicanalyses, findings as follows are obtained. (1) Phonoorthographicambiguity results in two forms: (a) the articulation of[h] which should be nonexistent between [a] and [u] or [i] and (b)the articulation of [a] instead of [i] in Indonesian names originallyJavanese. (1) Ortho-phonologic ambiguity results in two forms: (a)the writing of a final o instead of a in Indonesian names originallyJavanese and (b) the writing ofa final o instead of a in Indonesianterms originally Javanese. (3) Such cases ofambiguity are caused by(a) linguistic and (b) non-linguistic factors.Keywords: phonology, orthography, ambiguity, speech, writing,Indonesian